Design and fabrication of N-doped graphene decorated LiFePO4@C composite as a potential cathode for electrochemical energy storage. Issue 1 (January 2018) - Wang, Xiuling; Dong, Shuling; Wang, Hongxia
Abstract: Olivine-structured LiFePO4 @C nanoparticles grown on N-doped graphene (NG) sheets have been fabricated by using a simple sol-gel method with post calcinations. During the synthesis process, both the carbon film and NG sheets can inhibit the growth of LiFePO4 particles. Meanwhile, the constructed conductive network between the NG and carbon film can greatly enhance the electronic conductivity of LiFePO4 material. These unique properties lead to markedly improved lithium storage performance. The NG-decorated LiFePO4 @C (NG-LiFePO4 @C) composite presents high specific capacity (163.1 mAh g −1, 0.1 C) and excellent rate capability (118.6 mAh g −1, 10 C). Therefore, this NG-LiFePO4 @C composite can be regarded as a potential electrode for electrochemical energy storage.